1999
DOI: 10.1377/hlthaff.18.4.146
|View full text |Cite
|
Sign up to set email alerts
|

Where Are The Missing Elders? The Decline In Nursing Home Use, 1985 And 1995

Abstract: Findings from the 1995 National Nursing Home Survey suggest that elderly Americans are reducing their use of nursing home care. The numbers reflect a change in the role of the nursing home, as defined in this survey. By 1995 nursing facilities were increasingly focusing on patients with greater disability and postacute care needs. Preferred alternatives, most notably home-delivered care and assisted living, were likely filling the gap left by declining nursing home use. Better population-based studies are need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 1 publication
2
93
0
1
Order By: Relevance
“…Over time, residents and/or their families may learn that the initial home is not providing the desired levels or types of services as well as an alternative home could. Even if the initial choice was optimal when it was made, health and functional status can change (Bishop 1988;Gillen et al 1996).…”
Section: Does Quality Influence Consumer Choice Of Nursing Homes? Evimentioning
confidence: 99%
See 2 more Smart Citations
“…Over time, residents and/or their families may learn that the initial home is not providing the desired levels or types of services as well as an alternative home could. Even if the initial choice was optimal when it was made, health and functional status can change (Bishop 1988;Gillen et al 1996).…”
Section: Does Quality Influence Consumer Choice Of Nursing Homes? Evimentioning
confidence: 99%
“…The nature of nursing home care has changed over the last decade as the medical acuity and the frailty of nursing home residents have risen, while the length of stay for nursing home residents has decreased (Bishop 1999). Subsequently, more, fewer, or different specialized services (e.g., rehabilitative therapies, Alzheimer's units) may be appropriate for residents, and their needs may change dramatically as health status changes.…”
Section: Does Quality Influence Consumer Choice Of Nursing Homes? Evimentioning
confidence: 99%
See 1 more Smart Citation
“…But the past two decades have seen a radical shift in the composition of long-term care spending. Nursing home usage has fallen substantially; between 1985 and 1995, there was an 8.2% decline in the share of elderly who reported staying overnight in a nursing facility on a given day (Bishop 1999). And there has been a parallel substantial rise in long-term care delivered in the home setting, "home health care", over the same period, with an 82% increase in the share of Medicare beneficiaries who used home care and a 208% increase in the number of home care visits per user (U.S. Congress 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the US an increase of time spent living as a couple due to relatively increased male life expectancy could lead to a greater supply of informal care and a decrease of health and long-term care expenditure due to a decreased number of individuals living in nursing homes. 22,23 Changes in healthy life expectancy differ between the young old (< age 85) and the oldest old (age 85+). As for the former, the evidence is again mixed.…”
mentioning
confidence: 99%